Degradation of 2,3,7,8-TCDD by a consortium of bacterial strains isolated from heavil herbicide/dioxin contaminated soil in Bienhoa airbase - Quang Huy, Pham; Kim Thoa, Nguyen; Cam Ha, Dang Thi (Vietnam Journal of Biotechnology, 2020)
From two different soil sources in Bienhoa airbase (heavy herbicide/dioxin contaminated West-South region and bioremediated cell), five microbial strains were isolated and their 2,3,7,8-TCDD biodegrability in consortium was investigated. Based on the colony and cell morphological characteristics as well as 16S rRNA gene sequences, these strains were classified into 5 genera, including Methylobacterium (strain BHBi1), Hydrocarboniphaga (strain BHBi4), Agrobacterium (strain BHBi5), Bosea (strain BHBi7) and Microbacterium (strain BH09). Two strains BHBi7 and BHBi4 were the first representatives of the genera Bosea and Hydrocarboniphaga that were isolated from heavyly herbicide/dioxin contaminated soil. All five strains were able to grow well in mineral salt medium (MSM) supplemented with soil extract (SE) containing 2,3,7,8-TCDD (this congener is the main soil total compound toxicity) and other congeners, including PCDDs, PCDFs, 2,4,5-T, 2,4-D, PAHs and their intermediates. This microbial consortium degraded 2,537.34 ngTEQ/kg of 2,3,7,8-TCDD congener in soil, equivalent to 59.1% lost of total toxicity in comparison to the control without bacterial seeding (4,294.12 ng TEQ/kg). Such a high ratio of dioxin degradation by a bacterial consortium was reported here for the first time, contributing more evidences for convincing the successful dioxin bioremediation of “Active Landfill” technology at large scale in Z1 area at Bienhoa airbase, Dongnai, Vietnam.